Improving the E-Commerce Ecosystem to Support Online Sales for SMEs: A Case in the Leather Bag and Shoes Industry - Rahmania, Alifah Dian; Liquiddanu, Eko; Hisjam, Muh. (Universitas Brawijaya, Indonesia, 2024)
The pandemic has significantly impacted many shops closing and stopped production by artisans in the leather bag & shoe industry in Tanggulangin Sidoarjo. The development of e-commerce ecosystem studies shows that a deep understanding of the interactions between actors in this ecosystem can significantly improve online sales performance for SMEs. This study aims to identify the components and relationships between elements in the e-commerce ecosystem to support online sales in SMEs. This study uses the Delphi method with structured and in-depth interviews with several e-commerce SME experts. The components of the e-commerce ecosystem analyzed are marketing, platform, communication, payment, shipping & logistics, and productivity using descriptive analysis and framework visualization. The researchers proposed improving industry support components such as digital marketing training institutions, product photography and packaging design services, and product content creation services in the e-commerce ecosystem. This study is limited to the leather bag and shoe industry in Tanggulangin, Sidoarjo, which may restrict the generalizability of its findings to other sectors or regions. Additionally, the reliance on a small number of e-commerce experts and the lack of longitudinal testing for proposed solutions leave aspects like dynamic interrelationships and long-term sustainability underexplored.